Adherence to guideline-recommended therapies among patients with diverse manifestations of vascular disease - Chen, Debbie; Armstrong, Ehrin; Singh, Gagan; Amsterdam, Ezra; Laird, John (Vascular health and risk management, 2015)
Current guidelines recommend aspirin, statins, angiotensin-converting enzyme inhibitors (ACEIs), and smoking abstinence for all patients with vascular disease. There is little data on the variation in adherence to guideline-recommended therapies among patients with different clinical manifestations of vascular disease. To analyze the variation in adherence to guideline-recommended therapies among patients with diverse manifestations of vascular disease. We analyzed a comprehensive database of all patients with critical limb ischemia, claudication, acute limb ischemia, carotid artery stenosis, subclavian artery stenosis, renal artery stenosis, or mesenteric ischemia who underwent angiography between 2006 and 2013 at a multidisciplinary vascular center. Among 1,114 patients with vascular disease, adherence to guideline-recommended therapy at time of angiography included use of aspirin in 936 (84%), statins in 753 (68%), ACEIs in 673 (60%), and smoking abstinence in 788 (71%). A total of 335 (30%) patients utilized all four guideline-recommended therapies. Adherence to four guideline-recommended therapies was lowest among patients with acute limb ischemia (14%) and highest among patients with renal artery stenosis (37%). Among all patients with vascular disease, the range of adherence to individual guidelines was 64%-91% for aspirin, 43%-83% for statins, 49%-66% for ACEIs, and 47%-78% for smoking abstention. The majority of patients with diverse manifestations of vascular disease take aspirin and abstain from smoking while fewer patients are prescribed ACEIs and statins. Among the current recommendations, statins have the widest variation in adherence. Less than one-third of patients with diverse manifestations of vascular disease are prescribed all four guideline-recommended therapies.